UPAYA PEMBERDAYAAN MASYARAKAT DALAM MANAJEMEN SUMBERDAYA PERAIRAN SUNGAI BATANG HARI JAMBI TANTANGAN DAN SOLUSI - Ainin, Dewi Tumatul; Khasanah, Nur; Annajmi, Annajmi; Jannah Maruddani, Raoda Tul; Islamaya, Adinda (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
The management of water resources in the Batang Hari River faces significant challenges due to human activities and environmental changes. Empowering local communities is crucial to ensuring the sustainability of river resource management. This service activity aims to involve the community in collaboratively managing water resources (Batang Hari River) affected by ongoing degradation through a partnership network (stakeholders) to minimize challenges and formulate solutions for sustainable community empowerment in river resource management. The activities involve several partners and stakeholders, including the Korea-Indonesia Forest Cooperation Centre (KIFC), the Fish Hatchery Center of Muaro Jambi Regency, KJA farmers, academics, and the community of Rantau Panjang Village in Muaro Jambi Regency. The method used in this activity is a participatory approach through direct discussions, Focus Group Discussions (FGD), and qualitative data analysis. From the activities conducted, through workshops and participatory approaches, community awareness and participation in water resource management have significantly increased. Additionally, the community has developed new skills in sustainable resource management, and cooperation among stakeholders has been strengthened. This activity emphasizes the importance of community empowerment in achieving sustainable river resource management, contributing to environmental sustainability and the welfare of the local community.